Russia’s Vaccine Diplomacy in Central Europe: Between a Political Campaign and a Business Project (Czech Journal of International Relations, 2021)
Drawing on the concept of vaccine diplomacy, the article analyses Russia’s efforts to promote its Sputnik V vaccine and the repercussions this had in two Central European EU member states which authorized the use of the Russian vaccine. The authors argue that for Russia, Sputnik V promotion was significant both as a business project and as a political enterprise, as it was supposed to enhance Russia’s international status and help it in overcoming its post-Crimea isolation from the West. The results were mixed, however, as Russia’s international credibility had been undermined by its previous policies. Thus, in Hungary the vaccine managed to gain some traction thanks to a government that preferred importing non-EU certified vaccines as part of its larger policy of fostering closer ties with the authoritarian great powers in Eurasia. In Slovakia, the vaccine deal with Russia caused a political crisis but eventually resulted in a very poor performance of Sputnik V as compared to EU-certified vaccines.
Keywords: biopolitics; COVID-19; Hungary; Russia; Slovakia; Sputnik; vaccines